Medication-Related Experience of Deaf American Sign Language Users - Mariam Paracha; Ellen Wagner; Olivia Brumfield; Jonah Winninghoff; Jordan Wright; Jason Rotoli; Peter Hauser (SLACK Incorporated, 2023)
Background: Previous studies showed that deaf and hard-of-hearing (DHH) individuals have low health literacy related to prescription labels. This study examined the DHH's experience with understanding prescription labels and how technology can impact that experience. Objectives: The purpose of this qualitative study was twofold: (1) gain a more enhanced understanding of DHH experiences in understanding prescription labels with a focus on language needs, expectations, and preferences, and (2) assess the potential role of technology in addressing the communication-related accessibility issues which emerge from the data. Methods: In this study, 25 Deaf American Sign Language users who picked up a prescription from a pharmacy within the past year were interviewed. A thematic analysis, which included a systematic coding process, was used to uncover themes about their experiences picking up and using prescription medications. Key Results: Thematic analyses identified that medication-related experiences centered around themes: (1) medication information seeking; (2) comfort taking medication; (3) picking up medication; and (4) communication with the pharmacy team. A large contributor to the communication experience was the perception that the pharmacist was not being respectful. Regarding comfort taking medications, 12% of participants expressed a lack of understanding medications while taking medication. This led to participants largely using online resources when seeking medication information. This study also found that technology greatly aided the participants during this experience. Conclusion: This study recorded the experiences within the context of limited health literacy and aversive audism found that the DHH individual repeatedly encountered communication barriers, which may contribute to their poor medication literacy. Thus, future studies should explore how to leverage the potential benefits of technology to improve the pharmacy experience of the DHH, thereby improving medication literacy. [HLRP: Health Literacy Research and Practice. 2023;7(4):e215-e224.]